EFFECT OF THE ACTIVATION TIME OF PLATELET RICH PLASMA AND COLLAGEN ON THE LEVELS OF FIBROBLAST GROWTH FACTOR IN GINGIVAL CREVICULAR FLUID - Adisty Restu Poetri; Kwartarini Murdiastuti; Sudibyo sudibyo (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Gingival recession is a condition that occurs when the gingival margin is more apically than the cemento-enamel junction and causes the tooth root to open, so a root closure procedure is required. Platelet rich plasma (PRP) contains growth factors, including Fibroblast growth factor which plays a role in the process of angiogenesis and cell proliferation. The activation time is known to affect platelet count and FGF expression. The purpose of this study was to determine the effect of the activation time of platelet rich plasma and collagen on the expression of fibroblast growth factor in the gingival crevicular fluidMethod: The research sample was gingival crevicular fluid which was taken using paper point #30 for 30 seconds as many as 18 samples. Samples were taken before surgery, day 5 and day 7 after surgery. The samples were divided into 2 groups based on the activation time, 1 hour and 24 hours PRP-collagen. Changes in FGF levels were examined using ELISA. Repeated Meassure ANOVA test was conducted to compare the differences in each time observation and post hoc was performed to compare the differences between groups for each time observation.Result: There was no significant difference in FGF levels in the gingival crevicular fluid at each time and between groups.Conclusion: There was no effect of the activation time of platelet rich plasma and collagen on the levels of fibroblast growth factor in gingival crevicular fluid